The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.05.24.493307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A very long chain fatty acid responsive transcription factor, MYB93, regulates lateral root development in Arabidopsis

Abstract: Lateral roots (LRs) are critical to rhizosphere development in plants. Although the molecular mechanisms by which auxin regulates LR development has been studied extensively, many additional regulatory systems are thought to be involved. Based on the expression analysis of LTPG1 and 2, we found that they were specifically expressed at the developing LR primordium (LRP), and the number of LRs were reduced in these mutants. Because LTPG is a protein that transports Very Long Chain Fatty Acids (VLCFAs), we hypoth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…For YFP-cMYB50, YFP-cPMEI8, YFP-cUPB1 and CFP-cUPB1 cloning, the cMYB50, cPMEI8, and cUPB1 cDNA regions were amplified using forward and reverse primers containing the BamHI site just before the MYB50, PMEI8, or UPB1 termination codon. The cMYB50-Bam HI, cPMEI8-Bam HI, and cUPB1-Bam HI fragments were cloned into Aor51H1, and the Bam HI sites of YFP-Aor51H1-Bam HI-pDONR201 plasmids [16] and CFP-Aor51H1-Bam HI-pDONR201 plasmids [20], respectively.…”
Section: Plasmid Construction and Plant Transformationmentioning
confidence: 99%
“…For YFP-cMYB50, YFP-cPMEI8, YFP-cUPB1 and CFP-cUPB1 cloning, the cMYB50, cPMEI8, and cUPB1 cDNA regions were amplified using forward and reverse primers containing the BamHI site just before the MYB50, PMEI8, or UPB1 termination codon. The cMYB50-Bam HI, cPMEI8-Bam HI, and cUPB1-Bam HI fragments were cloned into Aor51H1, and the Bam HI sites of YFP-Aor51H1-Bam HI-pDONR201 plasmids [16] and CFP-Aor51H1-Bam HI-pDONR201 plasmids [20], respectively.…”
Section: Plasmid Construction and Plant Transformationmentioning
confidence: 99%
“…Recently, we reported that very long-chain fatty acids (VLCFAs) are involved in LR development through the regulation of the expression of the transcription factor MYB93 (Uemura et al, 2023). In addition to MYB93, ATML1, which has a START domain (a lipid-binding region), reportedly binds to very long-chain ceramides and plays a key role in epidermal differentiation (Abe et al, 2003; Lu et al, 1996; Sessions et al, 1999).…”
mentioning
confidence: 99%
“…The VLCFA levels decreased in kcs1-5 mutants, indicating that MYB93 is a novel transcription factor whose expression responds to VLCFA levels. MYB93 expression shows a specific response to fatty acid carbon chain length, with no response at C18 but a response to C20–C24 VLCFAs (Uemura et al, 2023). Moreover, genetic analysis has revealed that MYB93 is involved in the late stages of LR development by regulating the expression of several cell wall remodelling genes, such as expansins (Uemura et al, 2023).…”
mentioning
confidence: 99%
See 2 more Smart Citations